Cardiac Remodeling After Myocardial Infarction: Functional Contribution of microRNAs to Inflammation and Fibrosis - Varzideh, Fahimeh; Kansakar, Urna; Donkor, Kwame; Wilson, Scott; Jankauskas, Stanislovas S.; Mone, Pasquale; Wang, Xujun; Lombardi, Angela; Santulli, Gaetano (Frontiers in Cardiovascular Medicine, 2022)
After an ischemic injury, the heart undergoes a complex process of structural and functional remodeling that involves several steps, including inflammatory and fibrotic responses. In this review, we are focusing on the contribution of microRNAs in the regulation of inflammation and fibrosis after myocardial infarction. We summarize the most updated studies exploring the interactions between microRNAs and key regulators of inflammation and fibroblast activation and we discuss the recent discoveries, including clinical applications, in these rapidly advancing fields.